Covid-19 as a Catalyst for Strengthening Research Practice in BRICS’ Universities - Ntsofa Monyela; Neo Mofokeng (Journal of BRICS Studies)
South Africa’s National Development Plan 2030 (National Planning Commission, 2012) argues that there must be a simultaneous focus on research and teaching for South African universities to advance knowledge and society. However, since the dawn of COVID-19, most research focuses on teaching, leaving unattended research about doing and philosophising about research practice. Therefore, this paper rethinks ways of thinking and researching for postgraduate students who are based in South Africa’s (SA’s) historically disadvantaged institutions of higher learning. It proposes how the COVID-19 should bring about a paradigm shift in research methodologies and research practice, including the necessary supervision support for students. This social constructivist paper draws on the reflections of two postgraduate supervisors, and further reflects on broader paradigmatic issues within research. This paper relies strongly on the experiences of the authors as a primary source and also conceptually harvested from the existing literature. The autobiographic element study allows the researchers to explore the intersection between themselves and the subject they are studying, permitting the reader to understand this intersection and reflect on their own experiences (Given, 2008). There are two main arguments in this paper; 1) A call for re-centring the ethics of care and ethics of social responsibility as premises from which all research should start. This can be done by reflecting and exploring the first-hand experiences of those who are in Historically Disadvantaged Institutions (HDIs). 2) It is a call for equitable distribution of resources across BRICS universities, focusing primarily on the improvement of the HDIs which is consistent with BRICS’ multilateral developmental agenda.